2017
DOI: 10.1007/s00410-016-1324-y
|View full text |Cite
|
Sign up to set email alerts
|

Zircon record of fractionation, hydrous partial melting and thermal gradients at different depths in oceanic crust (ODP Site 735B, South-West Indian Ocean)

Abstract: Site 735B gabbro. Zircons from oxide gabbro are scarce and variable in composition consistent with their crystallization from melts formed by both fractionation of mafic magmas and hydrous remelting of gabbro cumulate. On the other hand, zircon from plagiogranite is abundant and each sample is characterized by compositional trends consistent with crystallization of zircon in an evolving melt. However, the trends are different between the plagiogranite at 500 m bsf and the deeper sections, which are interpreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The origin of melts forming felsic rocks in oceanic crust is diverse and is still debated. The felsic rocks are generally interpreted to have formed either from highly evolved fractionated melts in the late stage of crystallization of the gabbroic sequences, or by partial melting of pre-existing hydrothermally altered crustal rocks [6][7][8][9][10][11][12][13][14][15][16][17]. The intimate association of felsic rocks and oxide gabbros in slow-spreading ridge samples suggests another mechanism for the formation of the felsic melt, such as liquid immiscibility, as discussed and experimentally proved in References [18][19][20][21] and references therein.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…The origin of melts forming felsic rocks in oceanic crust is diverse and is still debated. The felsic rocks are generally interpreted to have formed either from highly evolved fractionated melts in the late stage of crystallization of the gabbroic sequences, or by partial melting of pre-existing hydrothermally altered crustal rocks [6][7][8][9][10][11][12][13][14][15][16][17]. The intimate association of felsic rocks and oxide gabbros in slow-spreading ridge samples suggests another mechanism for the formation of the felsic melt, such as liquid immiscibility, as discussed and experimentally proved in References [18][19][20][21] and references therein.…”
Section: Introductionmentioning
confidence: 90%
“…It is noteworthy that few data from Hole U1473A display various levels of REE concentrations, covering the entire variation range of those from Hole 735B. Pietranik and her colleagues in Reference [12] interpreted that these zircons were crystallized from the silica rich melts which derived by fractional crystallization of the parental mid-ocean-ridge basalt (MORB) at deeper sections of Hole 735B.…”
Section: Zirconmentioning
confidence: 99%
See 1 more Smart Citation
“…drilled samples from sheared peridotites of the Mid-Atlantic ridge, containing zircon crystals as accessory phase, have been interpreted as altered plagiogranite melt impregnations originating from hydrous partial melting of gabbroic intrusions in an oceanic shear zone (Cornen et al, 1999;Jöns et al, 2009;Pietranik et al, 2017). Consequently, the Ty-Lan chlorite schist, as well as similar samples from Ile de Groix and Bois-de-Cené, can be considered as fragments of ancient oceanic crust exposed in ophiolitic complexes.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Based on zircon compositions, however, Pietranik et al (2017) found two generations of felsic veins, one produced by hydrous partial melting in the upper 500 m of Hole 735B, and below 500 m, an older magmatic generation related to the oxide gabbros. These correspond to our Types II and I veins, respectively.…”
Section: Introductionmentioning
confidence: 99%